The effect of reaction atmosphere and growth duration on the size and morphology of boron nitride nanotubes. (6th August 2015) - Ahmad, Pervaiz; Khandaker, Mayeen Uddin; Amin, Yusoff Mohd; Muhammad, Nawshad; Usman, Ahmed Rufai; Amin, Muhammad
Abstract : Observations of BNNTs grown in the reaction atmosphere of argon, ammonia and nitrogen. Abstract : The effect of different reaction atmospheres is analyzed on the size and morphology of boron nitride nanotubes within a single and continuous growth duration of 180 min at 1200 °C. Field emission scanning electron microscopy micrographs show smaller and larger diameter boron nitride nanotubes in the range of 70–700 nm, with straight and curve parts. Some of the larger diameter boron nitride nanotubes have pipe-like morphologies at their top with the diameter in the range of 270–380 nm. High resolution transmission electron microscopy shows the tubular structure of the synthesized nanotubes with a non-uniform diameter. X-ray photoelectron spectroscopy shows B1s and N1s peaks at 190.3 eV and 398 eV for hexagonal boron nitride nature of the synthesized nanotubes. The Raman spectrum reports a higher intensity peak at 1370 (cm −1 ) that corresponds to E2g mode of vibration in hexagonal boron nitride.